Tracking the Impact of Local Wisdom in Sustainable Cultural Heritage Conservation: A Bibliometric Approach - Hayu Lusianawati; Sabil Mokodenseho; Dedi Gunawan Saputra; Yenik Pujowati (West Science Social and Humanities Studies, 2023)
In order to track the contribution of local wisdom to sustainable cultural heritage preservation, this study uses a bibliometric approach. A vast range of literature is covered by the analysis, including foundational works on political ecology, institutional ecology, ecological footprint, sustainable rural lifestyles, and systems thinking. Through the identification of clusters within the literature, the study reveals important topics including the preservation of biodiversity, sustainable tourism, and the incorporation of indigenous knowledge. The Brundtland Report and "Braiding Sweetgrass," among other notable publications, are recognized for having shaped the conversation on sustainability and the fusion of traditional knowledge with scientific understanding. A keyword analysis also indicates the prominence of terms like "Impact," "Local Wisdom," and "Tourism," indicating their importance in the industry. The results present a thorough summary of the field and are a useful resource for academics, decision-makers, and practitioners involved in the sustainable protection of cultural assets.